Advances in biodrying technologies for converting organic wastes into solid fuel. Issue 16 (10th December 2017) - Yang, Benqin; Hao, Zongdi; Jahng, Deokjin
ABSTRACT: Biodrying has emerged recently as an energy-effective technology for converting organic wastes into solid recovered fuel (SRF). In biodrying, water removal is achieved using metabolic heat produced from microbiological degradation of organics and forced airflow to promote heat and mass transfer. Factors affecting biodrying include moisture content (MC) and free air space (FAS) of the wastes, use of bulking agents, aeration rate, mechanical turning as well as microbial activities. These factors independently or collectively determine water removal capacities of various biodrying processes. In this review article, studies on these factors are surveyed extensively and reviewed. Additionally, details of reactor configurations, operation modes, and modeling studies on biodrying are summarized. Finally, health and environmental risks and their management associated with off-gases and final products of biodrying processes are discussed.